(untitled) (Journal of Global Accounting, 2023)
The study investigated the moderating role of earnings management on the relationship between environmental responsibility and financial performance of listed oil and gas firms in Nigeria. The specific objective of the study was to determine the extent to which earnings management moderates the relationship between environmental responsibility and return on assets of listed oil and gas firms in Nigeria. The study used ex-post facto research design. The population of the study was made up of ten (10) listed oil and gas firms in Nigeria from which a sample size of six (6) was purposively selected. Secondary data were obtained from the annual reports of the sampled firms. The period of study covered ten years (2012 to 2021). The moderated regression technique was used to validate the research hypothesis at 5% level of significance. Findings revealed that earnings management has an insignificant negative moderating effect on the relationship between environmental activities and the return on asset of listed oil and gas firms in Nigeria. In conclusion, when firms engage in earnings management, it not only impacts financial performance but also affects the perception of their commitment to environmental responsibilities. As such, the study recommends that firms should refrain from engaging in earnings management practices, as these could undermine the genuine positive impacts of their environmental responsibility efforts.